The Application of Iddah Maintenance for a Nusyuz Wife in Religious Court Verdicts - Rahmatillah, Nor Annisa; Ahmad, Ahmad (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This study aims to explore the rationale behind the Religious Court's decision to grant iddah maintenance to a wife considered nusyuz (disobedient), despite this conflicting with the provisions of Islamic law as stipulated in the Compilation of Islamic Law (KHI). This research uses a qualitative approach and normative analysis to examine the Religious Court decision number 0295/Pdt.G/2020/PA.Kab.Mn as a key case study. Primary data, consisting of court rulings, is analyzed to understand the arguments presented by the plaintiff and the defendant and the judge's reasoning in granting iddah maintenance despite the wife's proven nusyuz status. The findings indicate that, although Islamic law dictates that a nusyuz wife is not entitled to iddah maintenance, the court applied the principle of justice through progressive legal reasoning and the use of contra legem principles. The judge determined that granting iddah maintenance was a fair measure to protect the wife's rights after divorce, considering the social and humanitarian circumstances underlying the case.